Challenges and Support to HIV Care and Treatment of Female Sex Workers Living with HIV in Indonesia: A Mixed Method Study - Andriyani, Lia; Arina, Arina; Widihastuti, Asti; Nugroho, Adi (Unnes Journal of Public Health, 2021)
This study aims to describe the experience of female sex workers (FSWs) living with HIV in Indonesia during the care and treatment cascade, including the challenges and support associated with them. It was initiated by a trained community study team from OPSI, a national network for FSW community in the country. A mixed-method design was used, consisting of a cross-sectional survey and qualitative interviews conducted in four large cities in May and June 2019. Quantitative data were collected from 80 FSWs living with HIV, while qualitative interviews were conducted for 9 FSWs previously involved in the survey. Most of the FSWs were diagnosed with HIV at facility-based HIV testing services. While most FSWs delayed initiating their treatment, majority eventually commenced it. Overall treatment retention was fairly good, but some were being inconsistent or even stopped. However, individuals that have access to viral load test was low, leading to a small number of those confirming their viral suppression status. Conclusively, interventions directed to strengthen individuals’ literacy in HIV treatment and stigma management is recommended, as well as identification of maximum potential support systems around the FSWs.